Motivação para expectativa, entrada, permanência e saída: um estudo longitudinal no voluntariado da fundação Cidade viva. - Lemos, Samuel Lázaro Luz (2016)
This work comprises a longitudinal study that sought to analyze volunteers through the prism of the motivational factors of expectation, entrance, stay and exit from the Fundação Cidade Viva in the City of João Pessoa / PB. As the final product, we expected to provide information relevant to this institution on its praxis. Thus, it was used as the basis of theory of Structural Model of Motivation at Work Volunteer by Cavalcante (2012). It was then carried out an exploratory case study that designed quantitative questionnaires which were tabulated and evaluated by descriptive statistics and other tests such as the T test for independent samples and ANOVA (one way). As a result, it was detailed as the profile of the volunteers of the institution the prevalence of adult and married women in their 35 years, with monthly income above R$ 5,000.00. The pointed minimum education level was unfinished higher education. Usually a family member and / or friend have already performed volunteer work or currently does. Commonly they have participated in this type of work at another institution, but not at present time. It confirmed the hypothesis that voluntary motivations change with the passage of time, and analyzes suggests the possibility of conflict between the expectations of volunteers and the performance of this activity, because the indexes obtained as motivation compared in the four moments indicate that they fall moderately in the first year of operation to grow again since then. Furthermore, religion has emerged as the main tool to attract and maintain the workforce of the institution at issue which does not exclude the importance of other elements such as civic bias, learning objectives or identification with the organization, but suggests that the organization studied should pay attention to the religious element as its mainstay in their internal human resources policies.